CORRELATION ANALYSIS OF PARAMETERS OF LIPID METABOLISM, BODY MASS INDEX, INCLINATION TO RISK, AND STRESS TOLERANCE IN STUDENTS - Tatiana P. Bondar; Lubov I. Gubareva; Lubov S. Ermolova (Вестник Северо-Кавказского федерального университета, 2022)
Sex differences of lipid metabolism and body mass index (BMI) were installed. Tolerance to stress and inclination to risk increased with increasing of BMI. Correlation analysis of lipid metabolism and psychological indicators revealed interrelation between decrease stress level of young men and girls and increase of triglycerides blood concentration, increase of tolerance to stress and decline of general cholesterol and LDL-C concentrations.